Perencanaan Instalasi Pengolahan Air Limbah (IPAL) Pada Pabrik Tempe Di Kelurahan Sumur Dewa Kecamatan Selebar Kota Bengkulu - Edito Dwiantoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2022)
Waste is the remains of a business activity. Garbage is more synonymous with industrial-smelling things. The results of industrial processes that are no longer used are called industrial waste. However, there is one type of waste that is the most dangerous, namely B3 Waste which stands for Material, Hazardous and Toxic. One solution is to build a wastewater treatment plant using aerobic and anaerobic bio filters in the installed wastewater collection pond area. The method of data collection was carried out using a direct survey method at a predetermined research location. The data can be obtained through a direct survey at the research site. The collected data is then analyzed descriptively, namely: Water usage behavior, Waste water sources, Calculating the wastewater discharge produced in m3/day, Planning for wastewater treatment systems. From the results of data processing related to WWTP planning at the tempe factory located on Jalan Padat Karya 1A, Sumur Dewa Village, Selebar District, Bengkulu City, the following are the causes of pollution in the river due to one of them from processing tempeh production. 2 The solution for this treatment is WWTP planning using a septic tank. 3. The septic tank used for WWTP has a size of 8.1 m x 1.8 m. 4. Effective Processing Capacity Area1 3.05 m3